UTILIZATION OF INDONESIAN STRAIN ACTINOBACTERIA TO FACE THE THREAT OF BIOFILM AS THE MAIN CAUSE OF HEALTH CARE ASSOCIATED INFECTION - Cahyo, Bian Dwi; Retnowati, Dwi; Lisdiyanti, Puspita (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Health Care Associated Infection (HCAI) is one of the global infectious diseases that is expected to cause around 10 million deaths by 2050. One of the main causes is biofilm, an exopolysaccharide layer formed by bacteria, often found on medical equipment such as catheters, and has high resistance to antibiotics. Prevention efforts can be made through the search for antibiofilm compounds. Actinobacteria are known to produce potential bioactive compounds. This study utilized Actinobacteria strains from the waters of Bitung, North Sulawesi (code BT-023-026) to explore their antibiofilm potential through isolation, laboratory tests, and genetic analysis, followed by expert confirmation in the fields of intelligence, BPOM, and microbiology. The results show the great potential of BT-023-026 as an antibiofilm agent to prevent antibiotic resistance due to HCAI, while playing a strategic role in biodefense and strengthening health security through early warning and early detection.